2018
DOI: 10.1159/000495425
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Voltage-Dependent Calcium Channels with Pregabalin Exerts a Direct Neuroprotective Effect in an Animal Model of Multiple Sclerosis

Abstract: Background/Aims: Multiple sclerosis (MS) is a prototypical autoimmune central nervous system (CNS) disease. Particularly progressive forms of MS (PMS) show significant neuroaxonal damage as consequence of demyelination and neuronal hyperexcitation. Immuno-modulatory treatment strategies are beneficial in relapsing MS (RMS), but mostly fail in PMS. Pregabalin (Lyrica®) is prescribed to MS patients to treat neuropathic pain. Mechanistically, it targets voltage-dependent Ca2+ channels and reduces harmf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 52 publications
1
24
0
Order By: Relevance
“…However, the analgesic mechanism of PGB was explained by inhibition of excitatory neurotransmitter release in the pain pathway, facilitation in synaptic inhibition, decreasing glutamate cytotoxicity, and improvement of neuroinflammation. All occurred through Inhibition of alpha‐2‐delta‐1 subunit of voltage‐gated calcium channels (Hundehege et al., 2018; Joshi & Taylor, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the analgesic mechanism of PGB was explained by inhibition of excitatory neurotransmitter release in the pain pathway, facilitation in synaptic inhibition, decreasing glutamate cytotoxicity, and improvement of neuroinflammation. All occurred through Inhibition of alpha‐2‐delta‐1 subunit of voltage‐gated calcium channels (Hundehege et al., 2018; Joshi & Taylor, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Coordination impairment in VPA groups might occur through decreasing the dimension of the purkinje cells and decreasing the expression of calcium‐binding protein (Main & Kulesza, 2017). Since, some of the PGB effects are mediated through its effects on calcium channels (Hundehege et al., 2018; Joshi & Taylor, 2006), so maternal exposure to PGB can minimize prenatal VPA‐induced sex differences in beam balance test.…”
Section: Discussionmentioning
confidence: 99%
“…Pregabalin (Lyrica ® ) is prescribed to MS patients to treat neuropathic pain by targeting Cav [ 62 ] and, in addition, it could provide neuroprotection by inhibiting exaggerated Cav currents during excitotoxicity and neuroinflammation. Indeed, it has been demonstrated that Pregabalin treatment alleviates EAE symptoms in mice possibly by reverting, at neuronal level, intracellular Ca 2+ overload in EAE lesions [ 63 ]. However, in the same paper, the authors pointed to a significant reduction of hippocampal long-term potentiation in pregabalin-treated EAE mice, thus warning of potential side effects on memory and learning processes [ 58 , 63 ].…”
Section: Voltage-gated Channels In Oligodendroglial Cells and Myelinationmentioning
confidence: 99%
“…Consequently, this inhibition of voltage-gated calciumchannels diminishes the amount of available neurotransmitters in the synaptic cleft. When tested in an animal model of MS, pregabalin reduced the calcium-mediated neuronal cytotoxicity and neuronal damage (82). A similar attenuation of EAE was observed when mice were treated with the calcium antagonist nimodipine.…”
Section: Calcium As a Potential Therapeutic Target In Cns Autoimmunitymentioning
confidence: 54%